(2E)-2-[(2E)-3-Phenylprop-2-en-1-ylidene]-2,3-dihydro-1H-inden-1-one - Edward R. T. Tiekink; Seik Weng Ng; Hassan M. Faidallah; Khulud F. Al-Nemari; Abdullah M. Asiri (Acta Crystallographica Section E, 2012)
The title indan-1-one derivative, C18H14O, is planar with an r.m.s. deviation for all 19 non-H atoms of 0.098 Å. The conformation about each of the C=C bonds [1.343 (3) and 1.349 (3) Å] is E. Supramolecular layers in the bc plane, mediated by C—H...O and π–π [ring centroid–centroid distance = 3.5282 (15) Å] interactions, feature in the crystal packing.